Islamic State Central Africa Province (ISCAP) - Amanda Makosso; Auréole Collinet (The Journal of Intelligence, Conflict and Warfare, 2021)
The emergence of the Islamic State’s new affiliate—Islamic State Central Africa Province (ISCAP)—in Sub-Saharan Africa, has a devastating effect on the security and political landscape of an already fragile and unstable region. Based mainly on open sources, including think tanks, journals, U.N. reports, and news media, this paper attempts to understand the motivations and operations of the Islamic State fighters of this province and the dangers ISCAP presents to local and international actors.